Kepemimpinan Kristen dan Peran Gereja dalam Membentuk Identitas Remaja pada Era Globalisasi Berbasis Iman - Yedija Injili Damanik; Reni Triposa; Jeremia Joshua Christawan (GRAFTA: Journal of Christian Religion Education and Biblical Studies, 2026)
Globalization is reshaping adolescent identity formation through digital culture, pluralism, and contemporary social relations. Adolescents face a tension between Christian faith values and the dominant global popular culture. The church needs transformative leadership to shape adolescents’ Christ-centered identity, character, and life orientation. The phenomenon of digitalization exacerbates the identity crisis through social validation, moral relativism, and adolescent consumerism. This study aims to analyze the relationship between Christian leadership and the Church’s role in shaping faith-based adolescent identity. The study employs a qualitative literature review with descriptive-interpretive analysis of theological and social literature. The results indicate that relational leadership strengthens faith formation through exemplary behavior, dialogue, and mentoring of adolescents. The church, as a formative community, fosters character, spirituality, participation, and social responsibility among adolescents. This study proposes a Transformative Church Leadership Model for the formation of a contemporary faith-based adolescent identity. The model integrates Christ-Centered Identity, Relational Leadership, Participatory Community, Contextual Discipleship, and Digital-Cultural Engagement. Transformative church leadership strengthens Christian identity in the face of globalization, pluralism, and contemporary digital culture. Further research is recommended to test the model’s effectiveness through field studies and ongoing empirical approaches. Abstrak Globalisasi mengubah pembentukan identitas remaja melalui budaya digital, pluralitas, dan relasi sosial kontemporer. Remaja menghadapi ketegangan antara nilai iman Kristen dan budaya populer global yang dominan. Gereja membutuhkan kepemimpinan transformatif membentuk identitas, karakter, dan orientasi hidup remaja berbasis Kristus. Fenomena digitalisasi memperkuat krisis identitas melalui validasi sosial, relativisme moral, dan konsumerisme remaja. Penelitian bertujuan menganalisis hubungan kepemimpinan Kristen dan peran gereja membentuk identitas remaja berbasis iman. Penelitian menggunakan studi pustaka kualitatif dengan analisis deskriptif-interpretatif terhadap literatur teologis dan sosial. Hasil penelitian menunjukkan kepemimpinan relasional memperkuat formasi iman melalui keteladanan, dialog, dan pendampingan remaja. Gereja sebagai komunitas formatif menumbuhkan karakter, spiritualitas, partisipasi, dan tanggung jawab sosial remaja. Penelitian menawarkan Model Kepemimpinan Gereja Transformatif bagi pembentukan identitas remaja berbasis iman kontemporer. Model mengintegrasikan Christ-Centered Identity, Relational Leadership, Participatory Community, Contextual Discipleship, dan Digital-Cultural Engagement. Kepemimpinan gereja transformatif memperkuat identitas Kristiani menghadapi globalisasi, pluralitas, dan budaya digital kontemporer.